A novel TK/gE-deleted pseudorabies virus vaccine expressing CCL3L1 enhances humoral immunity by stimulating the dendritic cell-T follicular helper-germinal center axis - Lun Yao; Siwen Hao; Chengjun Zhang; Mengyun Jin; Qiao Hu; Qingping Luo; Guoyuan Wen; Hao Wu (Veterinary Microbiology, 2026)

Formation and application of soybean protein amyloid fibril-dextran-epigallocatechin gallate nanoparticles for interfacial engineering of lycopene-loaded Pickering emulsions - Changling Wu; Jie Hou; David Julian McClements; Li Li; Zhaogui Chen; Chengjun Liao; Kaixi Chen; Guangbiao Yan; Hao Hu; Guanyu Fang; Zhiping He; Xingquan Liu; et al. (Food Chemistry, 2026)

Ionic/hydrogen-bonding dual-network orchestration in sulfonated-OPBI via phytic acid-PEI nanoarchitectonics of PAFs for efficient proton transfer highways - Fei Chen; Xinyi Zong; Xianfeng Guan; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

Nanofiber ionic bridge framed quasi-solid polymer electrolyte with nanocellulose and PAF for improved low-temperature lithium battery - Jiayi Luo; Shenyuan Li; Yangyang Yu; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

Comparison of quality differences in Gastrodia elata wines fermented with different Saccharomyces cerevisiae and potential for sleep improvement in S. cerevisiae SY G. elata fermented wine - Zhiqiang Yi; Weizhong Hu; Huiying Li; Shuxin Zhou; Chengjun Jing; Quang D. Nguyen; Szilárd Kun; Szandra Klátyik; Zhirong Wang; Jianquan Kan; Muying Du (Food Bioscience, 2026)

Pediococcus acidilactici XZ106 ameliorates hyperglycemia in mice via steroid hormone and AMP-activated protein kinase pathway modulation - Shuxin Zhou; Weizhong Hu; Jianquan Kan; Zsolt Zalan; Chengjun Jing; Muying Du (Food Bioscience, 2026)

Steel plate-UHPC composite strengthening method for large-span prestressed concrete box girder bridges: Simulation, optimization, and case study - Tao Sun; Weikun He; Chengjun Tan; Jiahe An; Junde Hu; Lizhi Lu; Hua Zhao (Engineering Structures, 2026)

Influence of interface geometry on interfacial shear between precast UHPC and cast-in-place normal-strength concrete: Experimental and analytical investigation - Lei Tu; Weikun He; Hua Zhao; Chengjun Tan; Jiahe An; Junde Hu; Lizhi Lu (Engineering Structures, 2026)

Early Devonian alkaline volcanism in the North Qaidam, NW China: Insights into the Proto- to Paleo-Tethys tectonic transition - Mao Wang; Xianzhi Pei; Lei Pei; Zuochen Li; Chengjun Liu; Lili Xu; Ruibao Li; Li Qin; Xiao Wang; Nan Hu; Hao Lin (Journal of Asian Earth Sciences, 2026)

Multi-stage tectono-magmatic evolution of the Proto-Tethys Ocean: Constraints from Mid-Paleozoic granitoids in the East Kunlun-North Qaidam orogenic belt - Mao Wang; Xianzhi Pei; Lei Pei; Ruibao Li; Zuochen Li; Chengjun Liu; Youxin Chen; Nan Hu; Li Qin; Xiao Wang (Gondwana Research, 2026)

An interpretable deep learning framework for UHPC dry joint shear strength prediction under small sample regimes - Jingqi Cao; Weikun He; Chengjun Tan; Lei Tu; Suiwen Wu; Jiahe An; Junde Hu; Hua Zhao (Engineering Structures, 2026)

Linking plant traits, soil nutrients, climate and soil microbes in temperate grasslands - Yunlong Hu; Gukailin Ao; Liangchen Fu; Chengjun Ji; Hui Zeng; Biao Zhu (Plant and Soil, 2025)

Mitochondria-targeted nanoformulation inhibits periodontal ligament stem cells pyroptosis to promote periodontal tissue regeneration in periodontitis - Xinyuan Shao; Yuxiao Wang; Guichun Wang; Jingjing Hu; Yu Cheng; Chaoqi Wei; Zixuan Shu; Chengjun Peng; Yang Ding; Jian Guo; Zhifei Cheng; Shuangying Gui (Chemical Engineering Journal, 2025)

Climate, plant and microorganisms jointly influence soil organic matter fractions in temperate grasslands - Yunlong Hu; Liangchen Fu; Gukailin Ao; Chengjun Ji; Hui Zeng; Biao Zhu (Science of The Total Environment, 2025)

Mycorrhizal dominance influences tree species richness and richness–biomass relationship in China's forests - Suhui Ma; Guoping Chen; Qiong Cai; Chengjun Ji; Biao Zhu; Zhiyao Tang; Shuijin Hu; Jingyun Fang (Ecology, 2025)
Mycorrhizal associations drive plant community diversity and ecosystem functions. Arbuscular mycorrhiza (AM) and ectomycorrhiza (EcM) are two widespread mycorrhizal types and are thought to differentially affect plant diversity and productivity by nutrient acquisition and plant–soil feedback. However, it remains unclear how the mixture of two mycorrhizal types influences tree diversity, forest biomass, and their relationship at large spatial scales. Here, we explored these issues using data from 1247 plots (600 m 2 for each) across China's natural forests located mostly in temperate and subtropical regions. Both AM‐dominated and EcM‐dominated forests show relatively lower tree species richness and stand biomass, whereas forests with the mixture of mycorrhizal strategies sustain more tree species and higher biomass. Interestingly, the positive effect of tree diversity on biomass is stronger in forests with low (≤50%) than high AM tree proportion (>50%), reflecting a shift from the complementarity effect to functional redundancy with increasing AM trees. Our findings suggest that mycorrhizal dominance influences tree diversity and richness–biomass relationship in forest ecosystems.

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Thermal performance of multifunctional louver window integrated phase change material and spherical louver - Dong Li; Yanjiao Duan; Chengjun Zhang; Wanyu Hu; Xinpeng Yang; Qiang Fu; Müslüm Arıcı; Ruitong Yang; Xueyang Wang (Energy and Buildings, 2024)

Experimental and numerical investigation on deck system of a 102 m simply supported prestressed UHPC box-girder highway bridge - Sui Luo; Hua Zhao; Dongqin Qiao; Chengjun Tan; Xudong Shao; Jing Ma; Huangguo Qian; Zhilian Liao; Zhentao Hu; Cuizhu Zhou (Engineering Structures, 2024)

Concept and flexural performance of non-prestressed steel plate-UHPC-NC composite girder bridge - Lei Tu; Hua Zhao; Dongqin Qiao; Junde Hu; Chengjun Tan; Jing Ma; Zhentao Hu; Huiren Qiu; Xudong Shao (Engineering Structures, 2024)

Optimizing the indoor thermal environment and daylight performance of buildings with PCM glazing - Wanyu Hu; Yanjiao Duan; Dong Li; Chengjun Zhang; Hui Yang; Ruitong Yang (Energy and Buildings, 2024)

Polystyrene microplastics exposure reduces meat quality and disturbs skeletal muscle angiogenesis via thrombospondin 1 - Yun Yang; Hu Liu; Dongbin Zou; Fengjie Ji; Renlong Lv; Hongzhi Wu; Hanlin Zhou; Ao Ren; Tieshan Xu; Guanyu Hou; Chengjun Hu (Food Research International, 2024)

Evaluation of characteristics on the indoor dwelling environments of traditional villages in Hehuang area of China based on basic environmental parameters under remote sensing technology - Hongbin Ma; Chengjun Jing; Ang Hu; Lihua Ma (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Differential evolution with alternation between steady monopoly and transient competition of mutation strategies - Chenxi Ye; Chengjun Li; Yang Li; Yufei Sun; Wenxuan Yang; Mingyuan Bai; Xuanyu Zhu; Jinghan Hu; Tingzi Chi; Hongbo Zhu; Luqi He (Swarm and Evolutionary Computation, 2023)

A Review of Microplastics in China Marine Waters - Fenglei Gao; Jingxi Li; Jun Hu; Xianguo Li; Chengjun Sun (Journal of Ocean University of China, 2023)

Coupled anaerobic methane oxidation and metal reduction in soil under elevated CO 2 - Chenchao Xu; Naifang Zhang; Kaihang Zhang; Shuyao Li; Qing Xia; Jing Xiao; Maojun Liang; Weilei Lei; Junpan He; Gaiping Chen; Chengjun Ge; Xunhua Zheng; et al. (Global Change Biology, 2023)
Continued current emissions of carbon dioxide (CO 2 ) and methane (CH 4 ) by human activities will increase global atmospheric CO 2 and CH 4 concentrations and surface temperature significantly. Fields of paddy rice, the most important form of anthropogenic wetlands, account for about 9% of anthropogenic sources of CH 4 . Elevated atmospheric CO 2 may enhance CH 4 production in rice paddies, potentially reinforcing the increase in atmospheric CH 4 . However, what is not known is whether and how elevated CO 2 influences CH 4 consumption under anoxic soil conditions in rice paddies, as the net emission of CH 4 is a balance of methanogenesis and methanotrophy. In this study, we used a long‐term free‐air CO 2 enrichment experiment to examine the impact of elevated CO 2 on the transformation of CH 4 in a paddy rice agroecosystem. We demonstrate that elevated CO 2 substantially increased anaerobic oxidation of methane (AOM) coupled to manganese and/or iron oxides reduction in the calcareous paddy soil. We further show that elevated CO 2 may stimulate the growth and metabolism of Candidatus Methanoperedens nitroreducens , which is actively involved in catalyzing AOM when coupled to metal reduction, mainly through enhancing the availability of soil CH 4 . These findings suggest that a thorough evaluation of climate‐carbon cycle feedbacks may need to consider the coupling of methane and metal cycles in natural and agricultural wetlands under future climate change scenarios.

Unraveling the joint toxicity of transition-metal dichalcogenides and per- and polyfluoroalkyl substances in aqueous mediums by experimentation, machine learning and molecular dynamics - Guohong Liu; Xiliang Yan; Chengjun Li; Song Hu; Jiachen Yan; Bing Yan (Journal of Hazardous Materials, 2023)

Interactive effects of high temperature and crude protein levels on growth performance, nitrogen excretion, and fecal characteristics of broilers - Quanwei Liu; Jinghai Feng; Limin Wei; Chengjun Hu; Xinli Zheng; Ruiping Sun; Minhong Zhang (Tropical Animal Health and Production, 2022)

Dietary addition of fermented sorghum distiller’s dried grains with soluble improves carcass traits and meat quality in growing-finishing pigs - Huawei Li; Yehui Duan; Fugui Yin; Qian Zhu; Chengjun Hu; Lingying Wu; Peifeng Xie; Fengna Li; Runxi Cheng; Xiangfeng Kong (Tropical Animal Health and Production, 2022)

Simultaneous 3D Visualization of the Microvascular and Neural Network in Mouse Spinal Cord Using Synchrotron Radiation Micro-Computed Tomography - Liyuan Jiang; Chengjun Li; Miao Li; Xianzhen Yin; Tianding Wu; Chunyue Duan; Yong Cao; Hongbin Lu; Jianzhong Hu (Neuroscience Bulletin, 2021)
Effective methods for visualizing neurovascular morphology are essential for understanding the normal spinal cord and the morphological alterations associated with diseases. However, ideal techniques for simultaneously imaging neurovascular structure in a broad region of a specimen are still lacking. In this study, we combined Golgi staining with angiography and synchrotron radiation micro-computed tomography (SRμCT) to visualize the 3D neurovascular network in the mouse spinal cord. Using our method, the 3D neurons, nerve fibers, and vasculature in a broad region could be visualized in the same image at cellular resolution without destructive sectioning. Besides, we found that the 3D morphology of neurons, nerve fiber tracts, and vasculature visualized by SRμCT were highly consistent with that visualized using the histological method. Moreover, the 3D neurovascular structure could be quantitatively evaluated by the combined methodology. The method shown here will be useful in fundamental neuroscience studies.

Soil carbon persistence governed by plant input and mineral protection at regional and global scales - Leiyi Chen; Kai Fang; Bin Wei; Shuqi Qin; Xuehui Feng; Tianyu Hu; Chengjun Ji; Yuanhe Yang (Ecology Letters, 2021)
Elucidating the processes underlying the persistence of soil organic matter (SOM) is a prerequisite for projecting soil carbon feedback to climate change. However, the potential role of plant carbon input in regulating the multi‐layer SOM preservation over broad geographic scales remains unclear. Based on large‐scale soil radiocarbon (∆ 14 C) measurements on the Tibetan Plateau, we found that plant carbon input was the major contributor to topsoil carbon destabilisation despite the significant associations of topsoil ∆ 14 C with climatic and mineral variables as well as SOM chemical composition. By contrast, mineral protection by iron–aluminium oxides and cations became more important in preserving SOM in deep soils. These regional observations were confirmed by a global synthesis derived from the International Soil Radiocarbon Database (ISRaD). Our findings illustrate different effects of plant carbon input on SOM persistence across soil layers, providing new insights for models to better predict multi‐layer soil carbon dynamics under changing environments.

The decomposition rates of leaf litter and fine root and their temperature sensitivities are influenced differently by biotic factors - Shanshan Song; Xiaokang Hu; Jiangling Zhu; Tianli Zheng; Fan Zhang; Chengjun Ji; Jianxiao Zhu (Plant and Soil, 2021)

A combinatorial method to visualize the neuronal network in the mouse spinal cord: combination of a modified Golgi-Cox method and synchrotron radiation micro-computed tomography - Liyuan Jiang; Yong Cao; Xianzhen Yin; Shuangfei Ni; Miao Li; Chengjun Li; Zixiang Luo; Hongbin Lu; Jianzhong Hu (Histochemistry and Cell Biology, 2021)
Exploring the three-dimensional (3D) morphology of neurons is essential to understanding spinal cord function and associated diseases comprehensively. However, 3D imaging of the neuronal network in the broad region of the spinal cord at cellular resolution remains a challenge in the field of neuroscience. In this study, to obtain high-resolution 3D imaging of a detailed neuronal network in the mass of the spinal cord, the combination of synchrotron radiation micro-computed tomography (SRμCT) and the Golgi-cox staining were used. We optimized the Golgi-Cox method (GCM) and developed a modified GCM (M-GCM), which improved background staining, reduced the number of artefacts, and diminished the impact of incomplete vasculature compared to the current GCM. Moreover, we achieved high-resolution 3D imaging of the detailed neuronal network in the spinal cord through the combination of SRμCT and M-GCM. Our results showed that the M-GCM increased the contrast between the neuronal structure and its surrounding extracellular matrix. Compared to the GCM, the M-GCM also diminished the impact of the artefacts and incomplete vasculature on the 3D image. Additionally, the 3D neuronal architecture was successfully quantified using a combination of SRμCT and M-GCM. The SRμCT was shown to be a valuable non-destructive tool for 3D visualization of the neuronal network in the broad 3D region of the spinal cord. Such a combinatorial method will, therefore, transform the presentation of Golgi staining from 2 to 3D, providing significant improvements in the 3D rendering of the neuronal network.

Comparison of sedimentary organic carbon loading in the Yap Trench and other marine environments - Dong Li; Jun Zhao; Chenggang Liu; Chengjun Sun; Jianfang Chen; Jianming Pan; Zhengbing Han; Ji Hu (Journal of Oceanology and Limnology, 2020)

Effects of fresh and degraded dissolved organic matter derived from maize straw on copper sorption onto farmland loess - Sihai Hu; Cong Lu; Chengjun Zhang; Yuanjing Zhang; Hairui Yao; Yaoguo Wu (Journal of Soils and Sediments, 2016)

Influence of nitrogen form on the phytoextraction of cadmium by a newly discovered hyperaccumulator Carpobrotus rossii - Wuxing Liu; Chengjun Zhang; Pengjie Hu; Yongming Luo; Longhua Wu; Peter Sale; Caixian Tang (Environmental Science and Pollution Research, 2016)

Amplified solubilization effects of inherent dissolved organic matter releasing from less-humified sediment on phenanthrene sorption - Xiaoyan Zhang; Yaoguo Wu; Sihai Hu; Cong Lu; Chengjun Zhang (Environmental Science and Pollution Research, 2015)

Stoichiometric shifts in surface soils over broad geographical scales: evidence from C hina's grasslands - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Arindam Datta; Pin Li; Wenhong Ma; Anwar Mohammat; Haihua Shen; Huifeng Hu; Benjamin O. Knapp; Pete Smith (Global Ecology and Biogeography, 2014)
Aim The identification of stoichiometric flexibility is crucial for understanding carbon–nitrogen–phosphorus ( C – N – P ) interactions and ecosystem dynamics under a changing environment. However, current evidence of stoichiometric flexibility mainly comes from manipulation experiments, with little evidence from large‐scale observations. Location Alpine and temperate grasslands across northern C hina. Methods Using soil profiles derived from a historical national soil inventory and a contemporary regional soil survey across C hina's grasslands, we examined temporal changes in topsoil C : N : P ratios over recent decades. Results Topsoil C:N ratios of five major grassland types exhibited some flexibility but did not show significant changes over the sampling interval. Non‐significant changes in topsoil C : N ratios were observed both in alpine grasslands on the T ibetan P lateau and in temperate grasslands on the Inner Mongolian Plateau. Consistent with the relatively stable C : N ratios, the slope of the soil C – N stoichiometric relationship did not differ significantly between the two sampling periods. Soil N:P ratios in the surface layer increased significantly over the sampling interval, however, with an overall increase of 0.60 (95% confidence interval 0.58–0.62). A larger increase in soil N : P ratio was found in temperate grasslands on the I nner M ongolian P lateau than in alpine grasslands on the T ibetan P lateau. Moreover, the slope of the soil N – P stoichiometric relationship in these grassland ecosystems became steeper over the sampling interval. Main conclusions These results demonstrate the stability of topsoil C : N stoichiometry but variability in N : P stoichiometry over broad geographical scales, highlighting that soil C and N are tightly coupled, but N and P tend to be decoupled under a changing environment.

Comparative analyses of leaf anatomy of dicotyledonous species in Tibetan and Inner Mongolian grasslands - JianJing Ma; ChengJun Ji; Mei Han; TingFang Zhang; XueDong Yan; Dong Hu; Hui Zeng; JinSheng He (Science China Life Sciences, 2012)

Changes in topsoil carbon stock in the Tibetan grasslands between the 1980s and 2004 - YUANHE YANG; JINGYUN FANG; PETE SMITH; YANHONG TANG; ANPING CHEN; CHENGJUN JI; HUIFENG HU; SHENG RAO; KUN TAN; JIN‐SHENG HE (Global Change Biology, 2009)
Climate warming is likely inducing carbon loss from soils of northern ecosystems, but little evidence comes from large‐scale observations. Here we used data from a repeated soil survey and remote sensing vegetation index to explore changes in soil organic carbon (SOC) stock on the Tibetan Plateau during the past two decades. Our results showed that SOC stock in the top 30 cm depth in alpine grasslands on the plateau amounted to 4.4 Pg C (1 Pg=10 15 g), with an overall average of 3.9 kg C m −2 . SOC changes during 1980s–2004 were estimated at −0.6 g C m −2 yr −1 , ranging from −36.5 to 35.8 g C m −2 yr −1 at 95% confidence, indicating that SOC stock in the Tibetan alpine grasslands remained relatively stable over the sampling periods. Our findings are nonconsistent with previous reports of loss of soil C in grassland ecosystems due to the accelerated decomposition with warming. In the case of the alpine grasslands on the Tibetan Plateau studied here, we speculate that increased rates of decomposition as soils warmed during the last two decades may have been compensated by increased soil C inputs due to increased grass productivity. These results suggest that soil C stock in terrestrial ecosystems may respond differently to climate change depending on ecosystem type, regional climate pattern, and intensity of human disturbance.